Internationalization of higher education: Contributions of public policies to the legal Amazon Region (Desenvolvimento em Questão, 2025)
In Brazil, various strategies have been developed to promote the internationalization of higher education institutions through public policies. In this context, the present study aims to analyze public policies directed at the internationalization of higher education in the Brazilian Amazon region, based on a systematic literature review. The analyzed studies indicate that internationalization in this region faces significant challenges, especially due to the regional and socioeconomic inequalities that characterize the country. Such inequalities hinder equitable access to internationalization opportunities, leading to a concentration of resources and benefits in specific geographic areas or institutions. Therefore, it is essential to formulate public policies that take into account the specificities of the Legal Amazon, with strategies tailored to its realities, in order to ensure a more inclusive and balanced process of internationalization.
Keywords: Higher education; Postgraduate studies; Regional asymmetries